On Their Own: Contemporay Legends of Women Alone in the Urban Landscape - Tye, Diane (Ethnologies)

(untitled) (Association Canadienne d'Ethnologie et de Folklore, 2005)
This article explores the tension between women’s efforts to find time for themselves and traditional culture’s strong directives against women spending any time alone. Drawing on twenty-one contemporary legends from the Snopes website (http://www.snopes.com) that feature solitary female protagonists, it argues that the narratives demonstrate a gendered contestation of public space. Set in cars, hotels, shopping malls and in cyberspace, locations that sociologist Marc Augé (1995) describes as “non-places,” these legends warn of the dangers that await women if they venture into the world alone. In addressing the question of where women belong, the texts speak of female challenges to male domination of public spaces at the same time they reveal powerful male defenses.